PENGARUH MASA KERJA DAN USIA TERHADAP PRODUKTIFITAS KERJA KARYAWAN PT HEVEA MK I PALEMBANG - Rahmi Garmini (Masker Medika, 2023)
Introduction: Every company is always required to suppress and provide optimization to human resources so that they are able to have high skills or abilities. Employees are one of the assets that are very important for the continuity of an organization to get high productivity. One of the factors that have an influence on employee productivity is the factor of age and years of service. Research Method: The research method used is an analytic survey with a cross sectional approach with a sample of 49 workers. Data analysis used the chi-square test. Results: There is a relationship between years of service (p value = 0.032) and age (p-value = 0.003) with work productivity. Conclusion: Years of service and age affect the level of employee productivity.